TEACHERS’ PERCEPTIONS OF PROJECT-BASED LEARNING APPROACH IN ENGLISH LANGUAGE CLASSROOM OF WRITING SKILLS IN RECOUNT TEXT FOR THE EIGHTH-GRADE STUDENTS’ OF SMP ISLAM AL-AZHAR 18 SALATIGA - Rohmatika, Yulfa; Cahyaningsih, Laila Ayu; Famularsih, Sari (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2025)
This study investigates the perceptions of English teachers regarding the implementation of the Project-Based Learning (PJBL) approach for teaching writing skills, specifically recount text, to eighth-grade students at SMP Islam Al-Azhar 18 Salatiga. Employing a descriptive qualitative research design, the study aimed to explore teachers' views on the benefits, challenges, and overall effectiveness of PJBL in the context of the English language classroom. Data were collected through observation, documentation, and in-depth interviews with two English teachers. The findings indicate that both teachers hold highly positive perceptions of the PJBL approach, acknowledging its effectiveness in enhancing students' creativity, critical thinking, and engagement, especially in developing writing skills. However, the implementation is not without significant challenges, primarily related to time management and the difficulty of sustaining student motivation in regular classes. The research suggests that while PJBL is a valuable method, its full potential may be best realized with adequate support and in learning environments with conducive student characteristics. Overall, teachers recognize PJBL's strong potential to improve students' declining writing skills due to technology dependence. ABSTRAK Penelitian ini menyelidiki persepsi guru Bahasa Inggris mengenai penerapan pendekatan Project-Based Learning (PJBL) untuk mengajarkan keterampilan menulis, khususnya teks recount, kepada siswa kelas delapan di SMP Islam Al-Azhar 18 Salatiga. Dengan menggunakan desain penelitian kualitatif deskriptif, penelitian ini bertujuan untuk mengeksplorasi pandangan guru tentang manfaat, tantangan, dan efektivitas PJBL secara keseluruhan dalam konteks kelas Bahasa Inggris. Data dikumpulkan melalui observasi, dokumentasi, dan wawancara mendalam dengan dua guru Bahasa Inggris. Hasil penelitian menunjukkan bahwa kedua guru memiliki persepsi yang sangat positif terhadap pendekatan PJBL, mengakui efektivitasnya dalam meningkatkan kreativitas, berpikir kritis, dan keterlibatan siswa, terutama dalam mengembangkan keterampilan menulis. Namun, implementasi ini bukannya tanpa tantangan signifikan, terutama terkait manajemen waktu dan sulitnya mempertahankan motivasi siswa di kelas reguler. Penelitian ini menyarankan bahwa meskipun PJBL adalah metode yang berharga, potensi penuhnya mungkin paling baik dicapai dengan dukungan yang memadai dan di lingkungan belajar dengan karakteristik siswa yang kondusif. Secara keseluruhan, para guru mengakui potensi besar PJBL untuk meningkatkan keterampilan menulis siswa yang dilaporkan menurun akibat ketergantungan pada teknologi.